have some trouble with the following formula, anyone could provide the detailed demonstration? Corr1,2 = beta1*beta2*variance(market)/sd1*sd2

where did you find this?

under solution 3…

[1] cov (i,j) = beta (i) * beta (j) * variance (market) [2] corr (i,j) = cov (i,j) / [std (i) * std (j)] now substitute cov (i,j) from [1] to [2] and you get your formula: corr (i,j) = [beta (i) * beta (j) * variance (market)] / [std (i) * std (j)]

volkovv: could you pls let me know where do you get the [1] from? thanks! [1] cov (i,j) = beta (i) * beta (j) * variance (market)

volkovv: found it. committed to memory already…